2016
DOI: 10.1111/1440-1630.12318
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between time use in physical activity and gross motor performance of preschool children

Abstract: We conclude that paediatric occupational therapists should explain to parents the relationship between physical activity and motor development and advocate for developmentally positive physical activities for preschool children. Physical activity guidelines for Taiwanese preschoolers should be established immediately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
0
12
1
2
Order By: Relevance
“…The authors indicated that one possible mechanism is that children can use their whole musculature and power-related ability, which are connected to improving running velocity and jumping distance during outdoor play. Moreover, the duration of PA was associated with motor difficulty in pre-school aged children [51]. In this study, children who participated in PA less than 840 mins/wk were significantly more likely to experience motor difficulty (MABC-2; <5 th percentile) than children who participated in physical activity over 840 min/wk (OR=2.3; 95% CI:10, 5.1).…”
Section: Theories Of Motor Developmentmentioning
confidence: 60%
See 1 more Smart Citation
“…The authors indicated that one possible mechanism is that children can use their whole musculature and power-related ability, which are connected to improving running velocity and jumping distance during outdoor play. Moreover, the duration of PA was associated with motor difficulty in pre-school aged children [51]. In this study, children who participated in PA less than 840 mins/wk were significantly more likely to experience motor difficulty (MABC-2; <5 th percentile) than children who participated in physical activity over 840 min/wk (OR=2.3; 95% CI:10, 5.1).…”
Section: Theories Of Motor Developmentmentioning
confidence: 60%
“…Other studies investigated this association, focusing on type of PA [50] and duration of PA (51). In a study, physical activity (very active indoor and outdoor play) was significantly correlated with a specific type of motor skill development (throwing at a target, running speed; r=0.24, p = 0.01; r=0.21, p = 0.03) [50].…”
Section: Theories Of Motor Developmentmentioning
confidence: 99%
“…Positive correlation of mother's educational level and progress [48], as well as the duration devoted to doing activities have been confirmed in normal students [49]. Furthermore, a relationship was confirmed among mother's educational level, reduction of behavioral problems, and enhancement of social skills in children with specific requirements [46].…”
Section: Physical Trea Mentsmentioning
confidence: 89%
“…First, children's time spent on screen devices was reported by parents, which could be underreported when children were at childcare centres or parents were not at home. However, these items are derived from a validated questionnaire and have been used in other studies [73,74]. Second, pre-pregnancy behavioural data (including PA, TV and sleep duration) were limited to mothers' self-reports with potential recall bias.…”
Section: Discussionmentioning
confidence: 99%